Response of oil palm shell concrete slabs subjected to quasi-static and blast loads - Alengaram, Ubagaram Johnson; Mohottige, N.H.W.; Wu, C.; Jumaat, Mohd Zamin; Yap, Soon Poh; Wang, Z. (Elsevier, 2016)
A series of quasi-static and blast tests was conducted to investigate resistance capacity of concrete slabs in which conventional crushed granite aggregates were wholly replaced with oil palm shell (OPS) as a coarse aggregate. A control specimen using Normal Concrete (NC) using conventional aggregate of similar strength was also prepared and tested for comparison. Two types of OPS concrete (OPSC) slabs were developed-with and without steel fibres (SF) and tested. LVDTs, pressure transducers and accelerometers were used to record data of response of the slabs subjected to quasi-static load and blast loads of 1, 5 and 10 kg TNT. The recorded data were then analysed and compared and conclusions were made on the effectiveness of OPS as a coarse aggregate. It has been found that OPSC outperformed NC slab when subjected to 10 kg TNT as the ductile OPSC panel was intact and had no shrapnels. Through the ductility behaviour of OPSC, it exhibited multiple cracks and the impact resistance of OPS through its energy absorption due to fibrous content within OPS itself was visible both in crack pattern and in its propagation. Though OPS is of organic nature, its resistance to blast waves was observed as the huge fire ball created due to blast had no or little effect on the OPSC panels. The OPS Fibre Reinforced Concrete (OPSFRC) also exhibited blast resistance characteristics, but uneven distribution of fibres and harsh mix with 3% of steel fibres resulted in larger crack width and fibre pull-out failure. Overall, the behaviour of OPSC in blast resistance characteristics is noteworthy and further tests are required to envisage the use of appropriate fibre content in OPSC.